2015
DOI: 10.1002/alr.21594
|View full text |Cite
|
Sign up to set email alerts
|

Effects of desloratadine citrate disodium injection on rat models of ovalbumin‐induced allergic rhinitis: involvement of T‐cell responses modulation

Abstract: DLC (i.v.), given after an allergen challenge, improved Th1 cytokines level and restrained Th2 responses alleviating the symptoms of AR. Our results indicate that DLC injection may exhibit such effects through the modulation of T-cell responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…17 As we know, the immune system is a sensitive target for toxicologic factors in environment. 18 A perfect balance of Th1 and Th2 response is essential to a normal immune response. Th2 immunoresponse is the main mechanism for AR.…”
Section: Discussionmentioning
confidence: 99%
“…17 As we know, the immune system is a sensitive target for toxicologic factors in environment. 18 A perfect balance of Th1 and Th2 response is essential to a normal immune response. Th2 immunoresponse is the main mechanism for AR.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological pharmacokinetic studies have shown that it has higher solubility than other second-generation antihistamines with better safety, so it may have better efficacy for the treatment of chronic urticaria. 7,8 Currently, there are few studies on the effects of desloratadine citrate disodium on serum immunological function indices (IgE, C3 and C4), inflammatory factors (IL-4, IL-17 and IL-33), and chemokines (MCP-1, RANTES and Eotaxin) in patients with chronic urticaria.…”
Section: Introductionmentioning
confidence: 99%
“…Remodeling occurs in all inflammatory responses, and the mechanism and severity vary, depending on the disease. 8 Th2 immune response and air-way remodeling are well-known mechanisms responsible for AR 9,10 ; however, little is known regarding how PM2.5 exposure affects Th2related cytokines and the extent of nasal remodeling in AR.…”
mentioning
confidence: 99%